Regulating NETosis: Increasing pH Promotes NADPH Oxidase-Dependent NETosis - Khan, Meraj A.; Philip, Lijy M.; Cheung, Guillaume; Vadakepeedika, Shawn; Grasemann, Hartmut; Sweezey, Neil; Palaniyar, Nades (Frontiers in Medicine, 2018)
Neutrophils migrating from the blood (pH 7.35–7.45) into the surrounding tissues encounter changes in extracellular pH (pHe) conditions. Upon activation of NADPH oxidase 2 (Nox), neutrophils generate large amounts of H+ ions reducing the intracellular pH (pHi). Nevertheless, how extracellular pH regulates neutrophil extracellular trap (NET) formation (NETosis) is not clearly established. We hypothesized that increasing pH increases Nox-mediated production of reactive oxygen species (ROS) and neutrophil protease activity, stimulating NETosis. Here, we found that raising pHe (ranging from 6.6 to 7.8; every 0.2 units) increased pHi of both activated and resting neutrophils within 10–20 min (Seminaphtharhodafluor dual fluorescence measurements). Since Nox activity generates H+ ions, pHi is lower in neutrophils that are activated compared to resting. We also found that higher pH stimulated Nox-dependent ROS production (R123 generation; flow cytometry, plate reader assay, and imaging) during spontaneous and phorbol myristate acetate-induced NETosis (Sytox Green assays, immunoconfocal microscopy, and quantifying NETs). In neutrophils that are activated and not resting, higher pH stimulated histone H4 cleavage (Western blots) and NETosis. Raising pH increased Escherichia coli lipopolysaccharide-, Pseudomonas aeruginosa (Gram-negative)-, and Staphylococcus aureus (Gram-positive)-induced NETosis. Thus, higher pHe promoted Nox-dependent ROS production, protease activity, and NETosis; lower pH has the opposite effect. These studies provided mechanistic steps of pHe-mediated regulation of Nox-dependent NETosis. Raising pH either by sodium bicarbonate or Tris base (clinically known as Tris hydroxymethyl aminomethane, tromethamine, or THAM) increases NETosis. Each Tris molecule can bind 3H+ ions, whereas each bicarbonate HCO3− ion binds 1H+ ion. Therefore, the amount of Tris solution required to cause the same increase in pH level is less than that of equimolar bicarbonate solution. For that reason, regulating NETosis by pH with specific buffers such as THAM could be more effective than bicarbonate in managing NET-related diseases.